The concept of bildung Hegel's phenomenology and nineteenth century European novel - Gürle, F. Meltem. (Thesis (M.A.) - Bogazici University. Institute of Social Sciences, 1996., 1996)
This thesis presents an analysis of the pattern of Bildung (fonnation, development, education) in Hegel's Phenomenologie des Geistes (phenomenology of Mind/Spirit) upon a background of nineteenth century novel. Focusing on the tradition of romanti c realism in European novel from Dickens to Dostoyevsky, the analysis covers a CJit.ical review of Hegel's conception of Spirit, and a discussion of the problem of morality in Phenomenology.
Keywords: Consciousness.; Spirit.; European fiction -- 19th century.; Philosophy in literature.